A direct torque control algorithm for permanent magnet synchronous motors with minimum torque pulsation and reduced electromagnetic interference noise - Adam, Ali Ahmed; Gulez, Kayhan; Pastaci, Halit (TAYLOR & FRANCIS LTD, 2009)
In this work, a sensorless hysteresis direct torque control (HDTC) algorithm for a permanent magnet synchronous motor is described. The algorithm uses the output of two hysteresis controllers used in the traditional HDTC to determine two adjacent switching vectors per one sample time. The algorithm also uses the magnitude of the torque error, magnitude of the flux error and stator flux position to select the switching time for the selected vectors. The selection of the switching time utilises table structure which reduces the complexity of calculation. The simulation results of this proposed algorithm show adequate dynamic torque performance and considerable torque ripples reduction as well as lower current ripples and reduced electromagnetic interference noise level, as compared with HDTC.
Keywords: permanent magnet synchronous motor; hysteresis direct torque control; torque ripples; Engineering